Thin-cap fibroatheroma and large calcification at the proximal stent edge correlate with a high proportion of uncovered stent struts in the chronic phase. Issue 5 (August 2016) - Ueda, Tomoya; Uemura, Shiro; Watanabe, Makoto; Dote, Yoko; Goryo, Yutaka; Sugawara, Yu; Soeda, Tsunenari; Okayama, Satoshi; Kawata, Hiroyuki; Kawakami, Rika; Okura, Hiroyuki; Saito, Yoshihiko
Abstract : Objective: A high proportion of uncovered stent struts is associated with late stent thrombosis after drug-eluting stent (DES) implantation, which frequently results in myocardial infarction or death. However, the predictors of uncovered stent struts remain unknown. Here, using optical coherence tomography (OCT), we studied the baseline tissue characteristics of the target coronary segment and evaluated their influence on the neointimal coverage of the strut in the chronic phase. Methods: We analyzed 118 coronary lesions treated with OCT-guided DES implantation. OCT examinations of target lesions were performed before and after DES implantation, and tissue characteristics were evaluated within 5 mm outer segment of both stent edges. At follow-up, stent strut coverage was assessed within 5 mm inner segment from each stent edge. On the basis of the proportion of uncovered stent struts in the chronic phase, target segments were divided into poorly covered (the highest quartile with % uncovered struts, n =29) and well-covered (the remaining lower quartiles with % uncovered struts, n =89) groups. Results: Clinical parameters were similar between the two groups. On baseline OCT images, thin-cap fibroatheroma (TCFA) and large calcification were more frequently observed in the poorly covered group than the well-covered group (10.3 vs. 0.0%, P =0.0032, and 27.6 vs. 9.0%, P =0.017, respectively). Furthermore, multivariable analysis showed TCFA and large calcification at the proximal edge, but not at the distal edge, were predictors of uncover stent struts. Conclusion: TCFA and large calcification at the proximal stent edge are strong predictors of uncovered stent struts. OCT is useful for selecting stent landing sites in terms of future occurrence of uncovered stent struts.